1986
DOI: 10.1080/01490408609513080
|View full text |Cite
|
Sign up to set email alerts
|

Citizen and administrator perspectives of equity in the delivery of park services

Abstract: This paper addresses the issue of what constitutes fairness and equity in the allocation of park resources. Four alternative equity models are presented. A general population sample and a sample of park and recreation directors were surveyed to gain empirical insights into which of these models the two groups perceived to be most appropriate for governing the allocation of park resources. Both samples overwhelmingly supported the view that parks should be allocated to all areas equally, rather than on the basi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
28
1

Year Published

1991
1991
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 11 publications
2
28
1
Order By: Relevance
“…To some extent this study replicated the study reported by Wicks and Crompton (1986). Their Texas study was also part of a statewide survey and it also used a probability sample.…”
Section: Purpose Of the Studysupporting
confidence: 65%
See 3 more Smart Citations
“…To some extent this study replicated the study reported by Wicks and Crompton (1986). Their Texas study was also part of a statewide survey and it also used a probability sample.…”
Section: Purpose Of the Studysupporting
confidence: 65%
“…The study reported here incorporates five of the equity guidelines (Numbers 1, 3, 4, 5, and 6 in Table 1) and four of the five socioeconomic variables they used (level of education, age, ethnicity, and income level). However, this study extends the Wicks and Crompton (1986) study in four ways. First, it uses an expanded taxonomy of eight rather than five equity guidelines.…”
Section: Purpose Of the Studymentioning
confidence: 93%
See 2 more Smart Citations
“…Post 1970s, western countries put into effect a new public management reform policy emphasizing economics and the efficiency of supply (Wang, 2007). Five sub-concepts put forward by Lucy (1981) and three criteria proposed by Wicks and Crompton (1986) are representatives of the theories for the evaluation of fairness, but the essences are still the continuation of equality reform. The largest distribution efficiency of the urban green space was explored from the perspectives of geographic equity and space allotment fairness.…”
Section: Introductionmentioning
confidence: 99%